Discussion Of The Mining Methods Papers Presented At The New York Meeting, February, 1924 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1924)
CONTENTS PAGE CARMICHAEL, NORMAN, and KIDDIE, JOHN.-Development of Mine Transportation in Clifton-Morenci District. Discussed by Norman Carmichael, Charles Legrand, B. B. Gottsberger 1 BARER, THOMAS C.-Fresnillo - Glory-hole Mining Practice. Discussed by Charles A. Mitke, B. B. Gottsberger, E. R. Thomas, Enoch Perkins..: 3 BRADLEY, P. R.-Estimation of Ore Reserves and Mining Methods in Alaska Juneau Mine. Discussed by R. M. Raymond, A. H. Rogers, Enoch Perkins, H. G. Moulton 6 BIRCH, STEPHEN.-Geology and Mining Methods of the Kennecott and Beatson Mines. Discussed by R. M. Raymond, Alan M. Bateman, Enoch Perkins 8 LEES, CHARLES E.-Mining Methods and Costs at the Iron Cap Copper Co., Copper Hill, Ariz. Discussed by A. L. Walker, A. Neustaedter 10 BELL, CHARLES N. -Mining Methods of the Telluride District. Discussed by Charles S. Hurter 10 Development of Mine Transportation in Clifton-Morenci District Discussion of the paper of NORMAN CARMICHAEL and JOHN KIDDIE, presented at the New York Meeting, February, 1924, and issued, as. Paper No. 1310-M, with MINING AND METALLURGY, March, 1924. NORMAN CARMICHAEL.-We realized the objections too the gable-bottom car, but were almost forced to its adoption by the same reasons that caused us to retain the 20-in. gage. To use another car would have meant a vast number of changes, for our transportation system was quite extensive; all mine chutes and ore bins were arranged for that car. Had we been laying out, new works, many of our decisions would have been different. MEMBER.-If you were planning it now, would you not put in box bottom cars with a rotary dump? NORMAN CARMICHAEL.-We surely would. One objection to the gable-bottom car is the spill. No, matter how carefully the cars are kept up,: there is always leakage and spill. The cost of keeping and maintaining the cars in a good state of repair, so as to keep that loss at a minimum, is not necessary for a box-bottom car.